AN EMPIRICAL ANALYSIS OF THE RELATIONSHIP BETWEEN FIXED ASSETS INVESTMENT AND ECONOMIC GROWTH IN GUANGDONG PROVINCE - Jian Xin; Donglan Bao (STATMAT : JURNAL STATISTIKA DAN MATEMATIKA, 2021)
Based on the two sets of time series data of Guangdong Province’s GDP and fixed asset investment from 1990 to 2018, this paper establishes a VaR model, uses co-integration test, Granger causality test and other methods to conduct empirical analysis to study Guangdong’s fixed asset investment The relationship between economic growth. The analysis result shows that there is no long-term equilibrium relationship between fixed asset investment and economic growth in Guangdong Province. However, fixed asset investment is the Granger reason for economic growth, that is, fixed asset investment has a one-way effect on economic growth, and it can significantly promote economic growth. Economic Growth. In addition, a standard shock to the growth rate of fixed-asset investment has a relatively large impact on GDP, which also shows that fixed-asset investment has a certain role in promoting economic growth.